Post-disaster accessibility of basic health and social services in the first District of Zamboanga del Norte - Abad, Grace R.; Draper, Rolando D. (2015)
Healthy and socially redeveloped community pertains to the degree to which health and social services are effectively accessed. However, it is not possible to work towards complete equality in health and social services during and after disasters, as there are some factors of rendering the services that are beyond human influence. It is for this reason that this study was conducted to look into the post-disaster accessibility of basic health and social services in the first district of Zamboanga del Norte. It involved 390 respondents from the seven municipalities and one city of the first district of the province, namely: Dapitan City, La Libertad, Rizal, Sergio Osmeña, Sibutad, Mutya, Polanco, and Piñan. Results showed that the basic health and social services were rendered to the communities but distribution disparities were observed. The province therefore should target staffing efforts on medical professionals including those that specialize in health and social services delivery. Linkages that specialize should be enforced to increase the province’s facility to address post-disaster issues.
Keywords: Disasters; Mindanao studies